The Beta-adrenergic agonist, Ractopamine, increases skeletal muscle expression of Asparagine Synthetase as part of an integrated stress response gene program. Issue 1 (December 2018) - Brown, David; Ryan, Kevin; Daniel, Zoe; Mareko, Molebeledi; Talbot, Richard; Moreton, Joanna; Giles, Tom; Emes, Richard; Hodgman, Charlie; Parr, Tim; Brameld, John
Abstract Synthetic beta-adrenergic agonists (BA) have broad biomedical and agricultural application for increasing lean body mass, yet a poor understanding of the biology underpinning these agents is limiting further drug discovery potential. Growing female pigs (77 ± 7 kg) were administered the BA, Ractopamine (20 ppm in feed), or the recombinant growth hormone (GH), Reporcin (10 mg/48 hrs injected) for 1, 3, 7, 13 (n  = 10 per treatment, per time point) or 27 days (n  = 15 per treatment). Using RNA-sequencing and inferred pathway analysis, we examined temporal changes to theLongissimus Dorsi skeletal muscle transcriptome (n  = 3 per treatment, per time point) relative to a feed-only control cohort. Gene expression changes were affirmed by quantitative-PCR on all samples (n  = 164). RNA-sequencing analysis revealed that BA treatment had greater effects than GH, and that asparagine synthetase (Asns ) was the 5th most significantly increased gene by BA at day 3. ASNS protein expression was dramatically increased by BA treatment at day 7 (p < 0.05). The most significantly increased gene at day 3 was activating transcription factor 5 (Atf5 ), a transcription factor known to regulate ASNS gene expression. Gene and protein expression ofAtf4, another known regulator ofAsns expression, was not changed by BA treatment. Expression of more than 20 knownAtf4 target genes were increased by BA treatment, suggesting that BA treatment induces an integrated stress response (ISR) in skeletal muscle of pigs. In support of this, mRNA expression of sestrin-2 (Sesn2 ) and cyclin-dependant kinase 1 alpha (Cdkn1a ), two key stress-responsive genes and negative regulators of cellular growth, were also strongly increased from day 3 of BA treatment. Finally, tRNA charging was the most significantly enriched pathway induced by BA treatment, suggesting alterations to the translational capacity/efficiency of the muscle. BA-mediated changes to the skeletal muscle transcriptome are highly indicative of an integrated stress response (ISR), particularly genes relating to amino acid biosynthesis and protein translational capacity.